2022
DOI: 10.1111/ajt.16946
|View full text |Cite
|
Sign up to set email alerts
|

Incidence of cytomegalovirus infection in seropositive kidney transplant recipients treated with everolimus: A randomized, open-label, multicenter phase 4 trial

Abstract: Cytomegalovirus (CMV) persists as the most frequent opportunistic infection among solid organ transplant recipients. This multicenter trial aimed to test whether treatment with everolimus (EVR) could decrease the incidence of CMV DNAemia and disease. We randomized 186 CMV seropositive kidney transplant recipients in a 1:1 ratio to receive EVR or mycophenolic acid (MPA) in association with basiliximab, cyclosporin, and steroids and 87 in each group were analyzed. No universal prophylaxis was administered to eit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 29 publications
0
7
0
1
Order By: Relevance
“…64 There is increasing evidence that mTOR-Is have anti-CMV properties. 23,[77][78][79] They have indirect anti-viral activity and reduce the rate of CMV infection in CMV-seropositive organ transplant recipients. 80 mTOR-Is inhibit proliferation of infected cells by activating specific signaling pathways.…”
Section: Effect On Viral Infectionmentioning
confidence: 99%
See 1 more Smart Citation
“…64 There is increasing evidence that mTOR-Is have anti-CMV properties. 23,[77][78][79] They have indirect anti-viral activity and reduce the rate of CMV infection in CMV-seropositive organ transplant recipients. 80 mTOR-Is inhibit proliferation of infected cells by activating specific signaling pathways.…”
Section: Effect On Viral Infectionmentioning
confidence: 99%
“…There is increasing evidence that mTOR‐Is have anti‐CMV properties 23,77–79 . They have indirect anti‐viral activity and reduce the rate of CMV infection in CMV‐seropositive organ transplant recipients 80 .…”
Section: Introductionmentioning
confidence: 99%
“…A more recent Phase IV trial was conducted with 186 seropositive HCMV kidney recipients randomized (1:1) to receive EVR or MPA in combination with basiliximab, cyclosporine and steroids. In seropositive recipients, HCMV DNAemia is prevented by EVR treatment until it is no longer tolerated or stopped ( Kaminski et al, 2022a ). In addition, the same authors reported that the T-cell phenotype may offer a new biomarker for predicting post-transplant infection and classifying patients who should be eligible for EVR treatment ( Kaminski et al, 2022b ).…”
Section: Immunomodulating Moleculesmentioning
confidence: 99%
“…Immunosuppressive therapy (IST) is vital post SOT and response to pre‐emptive antiviral therapies may vary depending on choice of IST 33 . A randomized, open‐label study in seropositive kidney transplant recipients demonstrated greater benefit with pre‐emptive therapy when ciclosporin‐treated patients were receiving a mammalian target of rapamycin (mTOR) inhibitor, such as everolimus, rather than mycophenolic acid ( p < .0001) 34 . A clear lower rate of CMV infection has also been demonstrated in randomized trials of everolimus in heart transplant recipients 35,36 .…”
Section: Prevention: Antiviral Strategiesmentioning
confidence: 99%